Vráble, Slowakei: Herausbildung und Niedergang des frühbronzezeitlichen Siedlungszentrums – Untersuchungen zu Wirtschaft, Sozialstruktur und politischer Organisation eines Sozialverbandes und seines Umfeldes - Müller-Scheeßel, Nils; Reiter, Samantha; Radloff, Kai (e-Forschungsberichte des DAI, 2023)
The history of the development and decline of any settlement, be it prehistoric or modern cannot be understood in isolation. Research at the Early Bronze Age site of Fidvár by Vráble (southwest Slovakia) and its connections within the greater scope of its surrounding natural and human environment in the Žitava River Valley has been strongly geared towards this idea. Recent survey work at the settlement site at Fidvár confirmed comparative surface survey results from 2008, but also extended our knowledge of the site to the northeast. Further surveying of potential sites south of Fidvár in the Žitava River Valley were supported by a rigorous programme of augering as well as geomagnetic and topographical surveys. Of the newly examined sites, the most spectacular discovery was that of the contemporaneous settlement site of Hul. There, a ring-ditch with an extent of 98 × 80 m was discovered. Its extent (covering 0,3 ha) dovetails perfectly with our current models for the size and operation of social units during the Early Bronze Age in this part of Europe. Probably housing a social group ranging between 60–80 people, Hul likely mirrors the settlement at Fidvár before its expansion.